Predictors of Engagement in Family Mediation and Outcomes for Families that Fail to Engage. Issue 1 (22nd November 2016) - Morris, Megan; Halford, W. Kim; Petch, Jemima; Hardwick, David
Abstract : An important limitation to the effectiveness of family mediation in assisting separated parents is parents failing to engage in the mediation process. In 524 parents who presented to a telephone‐based mediation service, 113 (22%) initiating parents withdrew from mediation before the other parent was invited to participate, 241 (46%) initiating parents had respondent parents who declined to participate in mediation, and 170 cases (33%) completed mediation. We tested whether socio‐demographic variables, psychological distress, coparental acrimony, parenting problems, or children's behavioral difficulties predicted mediation engagement. High interparental acrimony predicted failure to engage in mediation, but none of the other variables predicted mediation engagement. We followed a sample of 131 families that did not mediate and found they showed elevated psychological distress, acrimony, parenting problems and child adjustment difficulties, which remained unchanged 6 months later. Further research is needed to explore strategies to enhance respondent parent engagement with mediation, and to address the negative outcomes for those separated families not proceeding with mediation.